Market characteristics, intra-firm coordination, and the choice of human resource management systems: Evidence from new Japanese data - Takao Kato; Hideo Owan (Institute for the Study of Labor (IZA), 2007)
This paper explores theoretically and empirically potentially important yet often-neglected linkage between task coordination within the organization and the structure of organization and bundling of HRMPs (Human Resource Management Practices). In so doing, we also provide fresh insights on the interplay between the firm's technological and output market characteristics and its choice of HRMP system. We begin with constructing a team-theoretic model and derive three task coordination modes: vertical control, horizontal coordination, and hybrid coordination. The model provides rich implications about complementarity involving task coordination modes, HRMPs, training and hiring, and management strategies, and illustrates how such complementarity is affected by the firm's technological and output market conditions. Guided by the theoretical exploration, we analyze unique data from a new survey of Japanese firms which provide for the first time data on newer forms of HRMPs adopted by Japanese firms (such as cross-functional offline teams and self-managed online teams). One novel finding (which is consistent with the theory) is that the adoption of both self-managed online teams and cross-functional offline teams usually arises in firms with shop-floor committees while the introduction of cross-functional offline teams alone often takes place in firms with joint labor-management committees. We also confirm implications from our theory that firms in more competitive markets are more likely to adopt both types of teams while firms facing more erratic price movement tend not to adopt self-managed online teams.
Keywords: 330; HRM systems; task coordination; teams; Personalwirtschaft; Unternehmensplanung; Unternehmensentwicklung; Marktstruktur; Theorie; Japan